Pengaruh Rasio Likuiditas, Solvabilitas dan Aktivitas Terhadap Profitabilitas Pada Perusahaan Transportasi Laut dan Logistik yang Terdaftar di Bei Periode 2019-2023 - Rahayu, Tia Septiana; Bella, Cinthya (Gorontalo State University, 2025)
This research was conducted to explore the influence of liquidity, solvency, and activity ratios on the profitability of companies in the maritime transportation and logistics sector listed on the Indonesia Stock Exchange (IDX). Profitability in this study is measured based on net profit recorded in the companies’ annual income statements. These three financial ratios—liquidity, solvency, and activity—are recognized as key parameters in evaluating a company’s financial health and performance, particularly in high-risk operational sectors such as maritime transport and logistics. This sector is heavily influenced by global market volatility, which can directly impact revenue. A quantitative method was employed in this study, with data sourced from annual reports spanning the period of 2019 to 2023. The research was motivated by the frequent fluctuations in profits and losses among companies in this sector, which are closely tied to external factors such as changes in fuel prices, global economic uncertainty, and cross-border trade dynamics.